(untitled) (Quaderni di Gargnano, 2022)
This article examines the novel-like structure of Dante’s Vita nuova, discussing its strategies for distancing the beloved object (Beatrice) both in space, according to perspective, and also in time, through memory. The structural debt of Petrarch’s Canzoniere to the Vita nuova is also considered. L’articolo prende in considerazione la struttura romanzesca della Vita nuova a partire dalle strategie di allontanamento dell’oggetto di desiderio (Beatrice) nello spazio, secondo la prospettiva, e nel tempo, attraverso la memoria. Viene inoltre considerato il debito strutturale del Canzoniere petrarchesco nei confronti della Vita nuova.